A review of some of the subjects in the report of the Royal Commission on Prisons in Ireland - MacDonnell, Hercules (Statistical and Social Inquiry Society of Ireland, 1885)
A review of some of the subjects in the Report of the Royal Commission on Prisons in Ireland has appeared to me a subject well worthy of consideration before this Society, dealing as it does with social problems of vast importance. It has struck me as very remarkable that such an important report has received such a limited share of public attention, since its appearance eight months ago. Except for brief comments in the daily press, and a few short articles in the medical journals dealing solely with the medical aspect of the question, there has been no notice whatever taken of what is an exceedingly able report, dealing with many points in an exhaustive manner, and recommending wholesale reforms.
Read before the Society, 12 May 1885
Keywords: Irish prisons; Reforming criminals; Crime; 314.15